Airway monocyte modulation relates to tumour necrosis factor dysregulation in neutrophilic asthma - Natalie M. Niessen; Peter G. Gibson; Jodie L. Simpson; Hayley A. Scott; Katherine J. Baines; Michael Fricker (ERJ Open Research, 2021)
Background Dysregulation of tumour necrosis factor-α (TNF-α) signalling is implicated in neutrophilic asthma. TNF-α signalling involves membrane-bound and soluble ligand (TNF-α) and receptors (TNFRs); however, little is known about how these proteins are altered in asthma. We hypothesised that intercompartment-, immune cell- and/or asthma inflammatory phenotype-dependent regulation could relate to TNF dysregulation in neutrophilic asthma. Methods Measurements were made in 45 adults with asthma (36 non-neutrophilic, 9 neutrophilic) and 8 non-asthma controls. Soluble TNF-α, TNF receptor 1 (TNFR1) and TNFR2 were quantified in plasma and sputum supernatant by ELISA, and membrane-bound TNF-α/TNFR1/TNFR2 measured on eosinophils, neutrophils, monocytes, and macrophages in blood and sputum by flow cytometry. Marker expression was compared between inflammatory phenotypes and compartments, and relationship of membrane-bound and soluble TNF markers and immune cell numbers tested by correlation. Results Soluble sputum TNFR1 and TNFR2 were increased in neutrophilic versus non-neutrophilic asthma (p=0.010 and p=0.029). Membrane-bound TNF-α expression was upregulated on sputum versus blood monocytes, while TNFR1 and TNFR2 levels were reduced on airway versus blood monocytes and neutrophils. Soluble TNFR1 and TNFR2 in sputum significantly correlated with the number of airway monocytes (p=0.016, r=0.358 and p=0.029, r=0.327). Conclusion Our results imply that increased sputum soluble TNF receptor levels observed in neutrophilic asthma relate to the increased recruitment of monocytes and neutrophils into the airways and their subsequent receptor shedding. Monocytes also increase TNF-α ligand expression in the airways. These results suggest an important contribution of airway monocytes to the altered inflammatory milieu in neutrophilic asthma.